“Women”: A New National Gender Model and the Representation Politics (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper interprets the media construction of a new gender model of woman in Serbia as a consequence of a change of dominant national ideology. An example is found in a talk show “Women” and the analysis is focused both on the traditional elements of the genre (its unbreakable connection to the idea of femininity and female public) and on the novelties which this particular talk show produces.
Keywords: gender model; representation; ideology; talk show